2022
DOI: 10.3390/foods11030460
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of Cordia and Ziziphus Gums with Respect to the Dough Properties and Baking Performance of Stored Pan Bread and Sponge Cakes

Abstract: The functionality of hydrocolloids of different origins, gum Cordia (GC), and gum ziziphus (GZ) on pan bread and sponge cake quality and their potential use in retarding the staling process have been studied. The effects of the gums were determined by assessing the pasting qualities of wheat flour slurry, dough properties, and the finished product. After 24 and 96 h of storage, investigations were conducted on the finished product. Micro-doughLab was used to assess dough mixing qualities, and a texture profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
4
13
0
Order By: Relevance
“…Alamri et al [ 24 ] suggested that the reduction in FV might be correlated with the lower amount of the total starch percentage in the blend due to the replacement with the gums. In line with our study, the reduction in the FV is also in line with the literature report in which ziziphus gum and Arabic gum lowered the viscosity of the wheat flour and starches [ 6 , 22 , 25 ].…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Alamri et al [ 24 ] suggested that the reduction in FV might be correlated with the lower amount of the total starch percentage in the blend due to the replacement with the gums. In line with our study, the reduction in the FV is also in line with the literature report in which ziziphus gum and Arabic gum lowered the viscosity of the wheat flour and starches [ 6 , 22 , 25 ].…”
Section: Resultssupporting
confidence: 93%
“…Apart from the 6% cactus gum addition, all the other levels of gums (acacia and cactus) better coated the starch granules and controlled their imbibition and rupturing and thus maintained the paste structure. In line with the current data, the lower BD was also noticed when the ziziphus and cordia gums were added to the wheat flour, improving the tolerance of the blend system [ 22 ].…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations